Rancang Bangun Sistem Bank Ternak Pada Bumdes Sarining Winangun Kukuh Menggunakan Framework Codeigniter - Hendra Maulana; Made Hanindia Prami Swari; I Putu Susila Handika; I Kadek Susila Satwika (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Livestock businesses in the Kukuh Village area, Tabanan District, Bali Province, have faced a big problem, namely the existence of a virus outbreak that causes many livestock to lose their lives every day. From this outbreak, it is hoped that the local government will be able to help deal with the problems faced so that livestock businesses can continue to carry out activities to raise and trade livestock under proper and profitable conditions. At present the local government has found a solution in dealing with this, the solution offered is to carry out training and guidance on raising livestock which is provided directly by veterinarians from the UPTD Puskeswan II Tabanan Tabanan Agriculture Office which covers the Kerambitan District. In addition, the government of Kukuh Bali village made a new policy to assist breeders to meet the needs for breeding capital through a new program called the livestock bank. The Livestock Bank is a service provided by the local government of the village of Kukuh Tabanan Bali to livestock businesses that still have doubts and fears about starting large livestock as well as to livestock businesses that do not have venture capital. The livestock bank program uses a gutter system, where the farmers will be given capital in advance by the BUMDes. The implementation of this web-based Livestock Bank application uses the PHP programming language with the CodeIgniter framework, the livestock bank application acts as an intermediary between the breeder and the financier, where the breeder acts as a negotiator to make it easier for breeders with insufficient managerial and administrative capabilities, and their business is not assessed. bankable by the lending financial institution.